LUCEMUS: An Innovative Educational Ludo Game for Enhancing Self-Efficacy in Musculoskeletal Injury First Aid among Rural School-Settings - Eky Madyaning Nastiti; Tasya Dwi Aulia Putri; Rida Darotin; Feri Ekaprasetia (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction:Musculoskeletal injuries are among the most common injuries experienced by school-age children, particularly in rural areas where environmental risks are higher and access to healthcare services and health education is limited. Low self-efficacy in providing first aid may hinder appropriate initial injury management, highlighting the need for innovative educational approaches to improve students’ confidence and preparedness Objectives: This study focused on evaluate effect of LUCEMUS, an educational Ludo-based board game incorporating musculoskeletal injury scenarios and first aid management using the Rest, Ice, Compression, and Elevation method, on students’ self-efficacy in providing first aid in rural school-settings Methods: A one-group pretest-posttest framewoek was employed within a quasi-experimental research design involving 32 students from a rural area. Partisipants’ self-efficacy was evaluated using General Self-Efficacy Scale used Likert scale. Participants completed a pretest, engaged in the LUCEMUS game in small groups under facilitator guidance, and completed a posttest. A paired-sample t-test was employed to analyse data. Results: The mean self-efficacy score increased from 28.24 before the intervention to 33.07 after the intervention. The Statistical analysis demonstrated significant improvement between pretest and posttest (p < 0.000), indicating that the LUCEMUS game demonstrated significant effect students’ self-efficacy in providing first aid for musculoskeletal injuries. Conclusions: LUCEMUS, an educational board game integrating Ludo with musculoskeletal injury first aid scenarios, effectively enhanced students’ self-efficacy in rural settings. This game-based learning approach has the potential to serve as an engaging and innovative health education strategy to strengthen adolescents’ confidence and preparedness in managing musculoskeletal injuries.